PENGARUH KARAKTERISTIK INDIVIDU DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI PADA PT. FEDERAL INTERNATIONAL FINANCE (FIF) CABANG AMBON - Ventje J Kuhuparuw (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2020)
This study aims to identify the effect of individual characteristics and Job Satisfaction on Organizational Commitment. The analytical method used in this research using Likert scale and multiple linear regression analysis using SPSS program based on the analysis, the model used to determine the organizational commitment based SPSS output is Y = 5654 + 0,536X1 + 0,321X2. Results of testing the hypothesis states that the variable Characteristics of individuals and job satisfaction positive and significant impact on organizational commitment with coefficient value of 5,654.